LINGUISTIC ATLASES OF BRAZIL: IS THERE PARASYNONYMY IN LEXICAL ITEMS? - Aragão, Maria do Socorro Silva de (2020)
The bases of Linguistic Geography consists in the study of the diatopic variations,or geographic, in the lexical level. In these variations, as well in the phonetic variations,we find the delimited marks of regional speeches.The affinity of significations, as says Pottier (1974,1987), that is found in thepara-synonymy, can situate the speaker in different sub-system as the special, temporal,situational or of technical.In this work we will present some examples of para-synonimies lexical items inthe Linguistic Atlas of Brazil.